Automatic interleaving technique using single interleaving bus for paralleling power converters. Issue 8 (1st August 2015) - Kudtongngam, Jasada; Liutanakul, Pisit; Chunkag, Viboon
Abstract : This study introduces a novel synchronous and encoding data technique on a single interleaving bus for automatic interleaving system of distributed power supply (DPS). Unlike the conventional interleaving techniques, this technique proposes replacing and removing one or more converter modules without interfering with the still‐working converters. With encoding data technique, each controller can determine the number of modules on the interleaving bus without any communication protocol. Besides, this technique is expected to perform a masterless control system and to enable automatic phase displacement, without any additional bus. A single current waveform on the interleaving bus carries information about the number of modules in its magnitude and phase displacements in its ramp that help the DPS in overcoming module failure and maintaining the operation. A prototype of the proposed automatic interleaving technique was designed, implemented and tested. The replacing and removing modules' scenarios with still‐working modules were demonstrated by the experimental results obtained on the four‐module interleaving prototype.